Exogenous carbohydrases and gut health in birds (Research, Society and Development, 2021)
Most feed ingredients for non-ruminant animals are of plant origin and may contain varying levels of non-starch polysaccharides (NAPs) in their composition. These are known to compromise, depending on ingredient inclusion levels, concentrations, and types in the feed, the performance and gut health of pigs and poultry. Carbohydrases are enzymes that degrade carbohydrates and have been used as alternatives to improve the utilization of feed sources that contain large amounts of PNAs, with positive results on energy utilization of the diet and reducing the negative effects of these compounds. Cellulases, xylanases, betaglucases, amylases, galactosities, among others have been supplemented in the feed of these animals and have shown to be effective in improving the morphometric characteristics, immune and microbial status of the intestine, with positive impacts on intestinal health and performance. Therefore, this study aimed to review the effects of the use of carbohydrase enzymes in poultry diets and their effects on gut health.